Some reproductive aspects of cartilaginous fish Raja clavataL., 1758(Elasmobranchii: Rajidae) from Syrian coast - Saad, Adib; Amin, Asaad; Alkusairy, Hasan H.; Sabour, Waad J. (Iraqi Journal of Aquaculture, 2021)
This study was performed on Thornback ray (Raja clavata L., 1758) through the period January 2013 - October 2014. It aimed to determine the reproductive cycle , fecundity and to determine median disc width at maturity (DW50 ) of this species. A total of 193 specimens, 107 females and 86 males were studiedfrom the Syrian coast. Median sizes (DW50) and (TL50) at maturity were estimated as DW50 = 333 mm, TL50 = 480 mm for males and DW50 = 406 mm, TL50 = 575 mm for females. This species posses a continuous reproductive cycle around the year in Syria marine waters. Fecundity was estimated between 87.7 and 175.4 egg cases per year.